New sorghum foods - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Recent periods of erratic and low rainfall in Africa are proving sorghum to be a more reliable grain crop than maize. As part of a governmentcoordinated approach to the problems of development in arid areas, the Kenya Industrial Research...